2023
DOI: 10.3389/fonc.2023.1143578
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization combined with apatinib and camrelizumab for unresectable advanced gastric or gastroesophageal junction cancer: a single-arm, single-center, retrospective study

Kunpeng Wu,
Yahua Li,
Zongming Li
et al.

Abstract: PurposeThis study aims to investigate the efficacy and safety of transcatheter arterial chemoembolization (TACE) combined with Apatinib and Camrelizumab for treating unresectable advanced gastric or gastroesophageal junction (G/GEJ) cancer.Material and methodsIn this study, data of patients with unresectable advanced G/GEJ cancer who received TACE combined with Apatinib and Camrelizumab from August 2018 to December 2021 was evaluated. After TACE, patients were given intravenous Camrelizumab 200mg every three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In the IAC group, the L. Su et al study achieved a 100% DCR as well as the highest median PFS of 11.0 (95% CI: 7.0–15.0) months [ 41 ]. In addition, there was the highest median OS of 20.0 months (95% CI: 13.6–26.4) in the study by Kunpeng Wu et al [ 37 ]. And from the 3 RCT trials we included, we found that immunotherapy combined with apatinib treatment was superior to immuno/apatinib alone, apatinib combined with chemotherapy, and immuno combined with chemotherapy in terms of median PFS and median OS [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the IAC group, the L. Su et al study achieved a 100% DCR as well as the highest median PFS of 11.0 (95% CI: 7.0–15.0) months [ 41 ]. In addition, there was the highest median OS of 20.0 months (95% CI: 13.6–26.4) in the study by Kunpeng Wu et al [ 37 ]. And from the 3 RCT trials we included, we found that immunotherapy combined with apatinib treatment was superior to immuno/apatinib alone, apatinib combined with chemotherapy, and immuno combined with chemotherapy in terms of median PFS and median OS [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%